The Influence of Servant Leadership on Organizational Citizenship Behavior from an Islamic Perspective: The Mediating Roles of Job Satisfaction and Emotional Intelligence (A Study of Islamic Junior High Schools in Sleman, Yogyakarta) - Zulfikar Fikry; Andriyastuti Suratman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study investigates the influence of servant leadership on organizational citizenship behavior (OCB) from an Islamic perspective, with emotional intelligence and job satisfaction as mediating variables among employees of State Islamic Junior High Schools (Madrasah Tsanawiyah Negeri, MTsN) in Sleman Regency, Indonesia. A quantitative approach was employed, with data collected from 112 employees through structured questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings indicate that servant leadership does not have a significant direct effect on OCB, suggesting that extra-role behaviors in Islamic educational institutions are primarily driven by intrinsic and spiritual motivations. However, servant leadership positively and significantly influences job satisfaction and emotional intelligence, both of which enhance OCB. Mediation analysis shows that emotional intelligence plays a significant mediating role in the relationship between servant leadership and OCB, whereas job satisfaction does not. These results underscore the importance of emotional intelligence as a key mechanism through which servant leadership fosters voluntary, prosocial, and value-based behaviors in an Islamic context. This study contributes empirical evidence to the literature on Islamic-based OCB and provides practical insights for human resource management in religious educational institutions.